Development of Solar Powered Portable Cooler Or Warmer - Hee, Chuen Haw; Jumaat, Siti Amely (Evolution in Electrical and Electronic Engineering, 2023)
This project focuses on the typical issues Malaysians encounter when participating in outdoor activities or purchasing food and drinks from street sellers. These problems include beverages staying cold for an extended amount of time and food going bad. Refrigerators and microwaves, which are commonplace alternatives, are bulky and difficult to transport. This is remedied by the introduction of a portable box using thermoelectric Peltier technology that weighs about 5 kg. With the help of this device, food and beverages will stay at the right temperature for a longer time, maintaining freshness. Based on the obtained result, the time taken for temperature inside the box to reach the desired point will be need round 30 minutes only. The temperature inside will maintain within 2ᵒC different. It also uses solar power as an alternate energy source, which aim to prolong the product operation time and lowers electricity costs. As the solar energy been applied, the product operation hours been extended from 11 hours to 16 hours. For outdoor activities and use by street vendors, the "Solar powered portable cooler and warmer" is a practical and effective option.